Intervening to prevent suicide at railway locations: findings from a qualitative study with front-line staff and rail commuters. Issue 2 (9th March 2022) - Katsampa, Dafni; Mackenzie, Jay-Marie; Crivatu, Ioana; Marzano, Lisa
Abstract : Background: For every suicide on the British railway network, at least six potential attempts are interrupted by front-line staff or rail commuters. However, the factors that maximise or hinder the likelihood and effectiveness of such interventions are poorly understood. Aims: The aim of the current study was to shed light on the experience of intervening to prevent a suicide at a railway location, including how and why people intervene, and their feelings and reflections in the aftermath. Method: In-depth interviews were carried out with rail commuters ( n = 11) and front-line railway staff ( n = 10) who had intervened to stop a suicide by train. Data were analysed thematically. Results: Participants had intervened to prevent suicide in several ways, both from afar (e.g. by calling a member of staff) and more directly (verbally or non-verbally), in some cases with no prior training or experience in suicide prevention, and often as a 'quick, gut reaction' given the limited time to intervene. In more 'reasoned' interventions, poor confidence and concerns around safety were the greatest barriers to action. Although often privy to their final outcome, most participants reflected positively on their intervention/s, stressing the importance of training and teamwork, as well as small talk and non-judgemental listening. Conclusions: Suicides in railway environments can present bystanders with little time to intervene. Potential interveners should therefore be resourced as best as possible through clear infrastructure help/emergency points, visibility of station staff and training for gatekeepers.